Heterojunction-Driven Stochasticity Bi-Heterojunction Noise-Enhanced Negative Transconductance Transistor in Image Generation - Han, Youngmin (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.